2013
DOI: 10.1111/1365-2435.12063
|View full text |Cite
|
Sign up to set email alerts
|

Foils of flexion: the effects of perch compliance on lizard locomotion and perch choice in the wild

Abstract: Summary1. Animals in the wild must navigate habitats that vary in structure and complexity. For arboreal animals, perch compliance (flexibility) is a common and variable characteristic, but the effects of perch compliance on arboreal behaviour and locomotion, specifically jumping, have only been examined for primates in the wild. 2. In this study, we observed jumping behaviour of green anole lizards (Anolis carolinensis) at a site with perches ranging from highly compliant palm leaflets to sturdy trunks and br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…). The substrates on which lizards perch have an important impact on their locomotor performance (Losos & Sinervo ; Gilman & Irschick ). We assessed the effects of inclination and roughness on performance because of the higher frequency of smooth, vertical substrates, such as buildings, fences and walls, in urban areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). The substrates on which lizards perch have an important impact on their locomotor performance (Losos & Sinervo ; Gilman & Irschick ). We assessed the effects of inclination and roughness on performance because of the higher frequency of smooth, vertical substrates, such as buildings, fences and walls, in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that habitat characteristics influenced locomotor behaviour in green anoles: despite using perches with a range of compliances, green anoles selectively jumped from less compliant (less flexible) perches (Gilman & Irschick ). Other research shows anoles tend to jump less often from broad surfaces (Pounds ; Losos & Irschick ) and when nearby perches are lacking (Moermond ; Avilés‐Rodríguez ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, compliant substrates absorb some of the mechanical work that would be otherwise employed to redirect and accelerate the CoM during steady locomotion, and compromise stability by undermining the animal's ability to estimate body orientation (MacLellan and Patla, 2006). Previous research has shown that increasing branch compliance significantly compromises the locomotor performance of leaping primates (Crompton et al, 1993;Demes et al, 1995;Warren and Crompton, 1997;Walker, 2005;Channon et al, 2011) and lizards (Gilman et al, 2012;Gilman and Irschick, 2013), and necessitates numerous postural and locomotor adjustments in orangutans (Thorpe et al, 2009;Myatt and Thorpe, 2011). However, relative to the breadth of research on the effects of substrate diameter, studies of how perch compliance affects quadrupedal gait mechanics are sparse (but see Stevens et al, 2001;GosselinIldari, 2010).…”
Section: Influence Of Substrate Compliance On Gait Kinematicsmentioning
confidence: 99%
“…A rigid Teflon rod, 9 cm long, was inserted within the tubing midway along the perch to provide a rigid area for frogs to jump from. The perch was stretched to 0, 2 and 4 cm beyond the slack length, creating three different compliance levels (2.3, 1.8 and 1.1 cm deformation under 1 N vertical load; unloaded resonant frequencies of 8.4, 9.5 and 12.1 Hz, respectively) within the range of arboreal substrate compliance observed in their introduced range (Gilman and Irschick, 2013). For rigid perches, frogs jumped from a wooden dowel of equal diameter.…”
Section: Perchesmentioning
confidence: 99%
“…Animals moving through natural habitats commonly encounter compliant substrates (Demes et al, 1995;Gilman et al, 2012;Gilman and Irschick, 2013), which yield when subjected to force, resulting in the absorption of mechanical energy. While some substrates, such as mud, may only dissipate energy, others, such as small-diameter plant branches, are elastic and may return a significant portion of their energy upon recoil (Cannell and Morgan, 1987).…”
Section: Introductionmentioning
confidence: 99%